The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1002/(sici)1097-4628(19991128)74:9<2124::aid-app2>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Formation of polyurethane membranes by immersion precipitation. II. Morphology formation

Abstract: Polyurethane membranes were prepared by an immersion precipitation process. The effects of dope concentration, coagulation bath composition, and the chemical structure of the polyurethane on the morphology of the membranes were studied. The degree of contraction was measured by quenching freshly formed polyurethane membranes in liquid nitrogen. A mechanism for the formation of membrane morphology during immersion precipitation is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 21 publications
3
22
0
Order By: Relevance
“…The thickness of the dense top layer is larger for the pure water bath, than for the water/NMP bath. Similar observation was reported by Kim et al [20]. Similarly, the porosity of the top layer is larger for the water/NMP bath relative to the water bath due to a slower quenching, indeed some evidence of the deep macrovoid structure is already present ( Figure 5).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The thickness of the dense top layer is larger for the pure water bath, than for the water/NMP bath. Similar observation was reported by Kim et al [20]. Similarly, the porosity of the top layer is larger for the water/NMP bath relative to the water bath due to a slower quenching, indeed some evidence of the deep macrovoid structure is already present ( Figure 5).…”
Section: Resultssupporting
confidence: 88%
“…Comparing with other conducting polymers such as polypyrrole in propylene carbonate electrolyte of which E is around 80 MPa, the low values of E reflect the porous nature of the samples. The higher value of E at the contraction state than that at the expansion state predicts the actuation strain will increase with the applied load [2,20]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The thermodynamic basis of the immersion precipitation method, which is the phase diagram of the polymer/solvent/nonsolvent system, had been well developed [8,9]. Some experimental and simulation works about the kinetics of immersion precipitation process had also been done [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Koenhen et al [10] found that the growth rate of the precipitation front decreased with increasing polymer concentration. But no details of the phase separation processes could be detected.…”
Section: Introductionmentioning
confidence: 99%
“…In 1979, Cohen et al [11] developed the first mass transfer model of immersion precipitation. Since then, many improvements had been made by, for example, Smolders and coworkers [12,13], McHugh and coworkers [14][15][16], Gryte and coworkers [17][18][19], Kumar and coworkers [20], Mayes and coworkers [21], Kim and coworkers [22], and Munari and coworkers [23], in the past decades. Because there are many properties difficult to control experimentally, modelling and simulations have been applied on immersion precipitation process to provide a crucial insight and design guidance in recent years [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%